(untitled) (Fiep Bulletin - online, 2014)
The Brazilian football has counted with a growing wave of selling the federative rights of their players over the last two decades. The average annual these negotiations comes close of 850 transfers, between the years of 2002 to 2007. I reviewed from quantitative data, which are the Brazilian that more work in this market, which countries capture more these players, and what are the areas that have the highest number of returns of athletes, or the regions that most Brazilian get back these players.